Development of a high-performance transtibial cycling-specific prosthesis for the London 2012 Paralympic Games - Dyer, B.; Woolley, H. (Prosthetics and Orthotics International, 2016)
Background and Aim: It has been reported that cycling-specific research relating to participants with an amputation is extremely limited in both volume and frequency. However, practitioners might participate in the development of cycling-specific prosthetic limbs. This technical note presents the development of a successful design of a prosthetic limb developed specifically for competitive cycling. Technique: This project resulted in a hollow composite construction which was low in weight and shaped to reduce a rider`s aerodynamic drag. Discussion: The new prosthesis reduces the overall mass of more traditional designs by a significant amount yet provides a more aerodynamic shape over traditional approaches. These decisions have yielded a measurable increase in cycling performance. While further refinement is needed to reduce the aerodynamic drag as much as possible, this project highlights the benefits that can exist by optimising the design of sports-specific prosthetic limbs. Clinical relevance: This project resulted in the creation of a cycling-specific prosthesis which was tailored to the needs of a high-performance environment. Whilst further optimisation is possible, this project provides insight into the development of sports-specific prostheses.